2016
DOI: 10.1111/1759-3441.12148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Central Bank Intervention in the Foreign Exchange Market: Evidence from India Using an Event Study Approach

Abstract: The analysis of effectiveness of central bank intervention has yielded mixed empirical evidence and remains inconclusive to date. Managed float regimes can offer vital clues on this debate. We study the impact of central bank intervention on exchange rate direction, volatility and misalignment using data from the Indian managed float, characterised by consistent intervention by India's central bank. The paper uses event study methodology given the clustered and non‐stochastic nature of intervention. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Some documented bank intervention does not significantly determine the exchange-rate volatility [1], but there were some significant evidences that it determined the exchangerate volatility [2] and [3]. The Central Bank intervention efforts are intended to reduce the exchange-rate volatility of a currency [4], [5], but there are some documents that it actually increases the exchange-rate volatility [6]. Literature found that productivity determines the exchangerate volatility, but still empirically it proved different results.…”
Section: Introductionmentioning
confidence: 99%
“…Some documented bank intervention does not significantly determine the exchange-rate volatility [1], but there were some significant evidences that it determined the exchangerate volatility [2] and [3]. The Central Bank intervention efforts are intended to reduce the exchange-rate volatility of a currency [4], [5], but there are some documents that it actually increases the exchange-rate volatility [6]. Literature found that productivity determines the exchangerate volatility, but still empirically it proved different results.…”
Section: Introductionmentioning
confidence: 99%